Upstream sources of the Denmark Strait Overflow: Observations from a high-resolution mooring array. (June 2016) - Harden, B.E.; Pickart, R.S.; Valdimarsson, Héðinn; Våge, Kjetil; de Steur, Laura; Richards, Clark; Bahr, Frank; Torres, Dan; Børve, Eli; Jónsson, Steingrímur; Macrander, Andreas; Østerhus, Svein; et al.
Abstract: We present the first results from a densely instrumented mooring array upstream of the Denmark Strait sill, extending from the Iceland shelfbreak to the Greenland shelf. The array was deployed from September 2011 to July 2012, and captured the vast majority of overflow water denser than 27.8 kg m −3 approaching the sill. The mean transport of overflow water over the length of the deployment was 3.54±0.16 Sv. Of this, 0.58 Sv originated from below sill depth, revealing that aspiration takes place in Denmark Strait. We confirm the presence of two main sources of overflow water: one approaching the sill in the East Greenland Current and the other via the North Icelandic Jet. Using an objective technique based on the hydrographic properties of the water, the transports of these two sources are found to be 2.54±0.17 Sv and 1.00±0.17 Sv, respectively. We further partition the East Greenland Current source into that carried by the shelfbreak jet (1.50±0.16 Sv) versus that transported by a separated branch of the current on the Iceland slope (1.04±0.15 Sv). Over the course of the year the total overflow transport is more consistent than the transport in either branch; compensation takes place among the pathways that maintains a stable total overflow transport. This is especially true for the two East Greenland Current branches whose transports vary out of phase with each other on weekly and longer time scales. We argue that wind forcing plays a role in this partitioning. Abstract : Highlights: Overflow transport upstream of Denmark Strait measured as 3.54±0.16 Sv over one year. Two main sources of overflow: EGC (2.54±0.17 Sv) and NIJ (1.00±0.17 Sv). Total overflow more consistent than either branch: pathways compensate for each other. EGC split between Greenland and Iceland slopes in time-varying manner over year. Wind forcing proposed as a mechanism for this splitting.